PENGABDIAN KEPADA MASYARAKAT DI KOTA KUPANG: INFESTASI FASCIOLA SP. PADA HEWAN KURBAN DI MASJID AL-ISTIQOMAH - Pandarangga, Putri (Universitas Nusa Cendana, 2023)
The Eid al-Adha celebration is a Muslim religious celebration when Muslims are financially capable of sacrificial animals such as cows and goats and then share the meats with the community. However, zoonotic diseases, which can attack humans, become a threat. Therefore, a veterinarian was needed to check whether the meat from 11 cows and 16 goats at Al-Istiqomah mosque was free from zoonotic diseases and safe for consumption by the public. This activity was divided into three stages: antemortem examination, post-mortem examination, and dissemination of knowledge about zoonotic animal diseases. The ante-mortem examination result showed that all animals were eligible for slaughter. However, after post-mortem examination, three livers had to be rejected due to Fasciola sp infestation. This worm could attack humans through uncooked liver. The findings from this post-mortem examination prevented the possibility of 500 heads of families getting liver that contained Fasciola sp.